The Impact of Atrial Left-to-Right Shunt on Pulmonary Hypertension in Preterm Infants with Moderate or Severe Bronchopulmonary Dysplasia - Eui Kyung Choi; Young Hwa Jung; Han-Suk Kim; Seung Han Shin; Chang Won Choi; Ee-Kyung Kim; Beyong Il Kim; Jung-Hwan Choi (Elsevier, 2015)
Bronchopulmonary dysplasia (BPD)-associated pulmonary hypertension (PH) is a well-known complication of prematurity; however, the additional impact of a left-to-right interatrial shunt on this condition remains poorly understood. The aim of the present study was to identify the significance of atrial left-to-right shunt lesions in PH infants with moderate or severe BPD. Methods: The medical records of 383 preterm infants (gestational age of < 32 weeks) who were diagnosed with BPD between 2005 and 2013 were retrospectively reviewed. Baseline characteristics such as interatrial shunts and outcomes were compared between the infants who developed PH (n = 50) and infants who did not (n = 144). Infants with hemodynamically significant residual patent ductus arteriosus were excluded. Among the infants diagnosed with PH (n = 50), the outcomes were compared between the patients with (n = 21) and without atrial shunts (n = 29) at 36 weeks corrected postmenstrual age. Results: Fifty (15%) preterm infants with BPD were diagnosed with PH. The number of infants with a history of atrial shunt lesions was significantly higher in the PH group than in the non-PH group (42% vs. 15.3%, respectively). The adjusted odds ratio for PH in the atrial shunt group was 3.8 (95% confidence interval, 1.8-8.0), compared to PH-BPD infants without an atrial shunt. Conclusion: The presence of an atrial left-to-right shunt was associated with PH in preterm infants with moderate or severe BPD. Close follow up is needed for infants with interatrial shunts, and a more tailored prognostic evaluation and treatment are recommended.